Effectiveness of Gluteus Maximus Strengthening on Gait in Patients with Hemiparesis (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Seventy five per cent of patients who outlive stroke have inadequacies whilst walking andthe hemiparetic gait is the most prevalent form of walking. The asymmetric pattern of walking is mostcommonly seen in hemiparetic gait.Aim and Objectives: To find the effectiveness of gluteus maximus strengthening on gait in patients withhemiparesis.Materials and Method: The hemiparetic patients were assessed for the MMT and gait, prior to the treatment.The muscle strength and gait was assessed by Manual Muscle Testing and objective method respectively.Subjects signed the consent form then total number of three exercises were given-i)Standing leg lifts withtrunk supported, ii) Quadruped leg lifts, iii) Standing extension.Statistical analysis was done once the datawas collectedResults: In this study the gluteus maximus strengthening had effect on the gait of the hemiparetic individuals.The gait parameters taken in this study step length, step width, stride length, cadence and speed significantlyincrease after the treatment.Conclusion: On the basis of the result of this study, it was concluded that the strengthening of gluteusmaximus muscle has effect on gait in patients with hemiparesis. The gait parameters taken in this study suchas step length, step width, stride length, cadence and speed has increase in the averaged values before andafter treatment.